Análise químico-farmacêutica do ácido fusídico em formulações de creme - Curbete, Mariane Machado [UNESP] (2015)
Fusidic acid is an antimicrobial steroid, indicated in the treatment of serious infections caused by microorganisms of the genus Staphylococcus and other Gram-positive bacteria species, including resistant species to penicillin and other antimicrobials. Research involving the development of more practical analytical methods are relevant to optimize the analysis in the pharmaceutical industry and secure the quality of commercialized product. Thus, this study aimed to develop faster analytical methods, safer for operators, economical and easy to perform, compared to the methods described in the literature for the determination of fusidic acid in the pharmaceutical form of dermatological cream. Fusidic acid was analyzed for its organoleptic and physical-chemical characteristics. Qualitative analysis was performed method by spectrophotometric absorption in the visible region and by thin layer chromatography. For quantification of fusidic acid, were developed and validated two methods: stability indicative method by high performance liquid chromatography, in the concentration range from 5.0 to 95.0 μg mL-1, using mobile phase composed by acetonitrile and water (72:28, v/v), pH 3.5 adjusted with acetic acid and at a wavelength at 210 nm, this method presented average retention time of 8.12 minutes, accuracy of 101.22% and content of 104%; microbiological assay by turbidimetric method, in the concentration range from 0.25 to 2.25 μg mL-1, using casoy broth and 6% of the microorganism Staphylococcus epidermidis ATCC 12228, whose accuracy and mean percentage were 101.95% and 104.60%, respectively. The methods were validated according to ICH guidelines and Brazilian legislation and shown to be accurate, robust, selective, accurate and equivalent to quantify the fusidic acid, at a significance level of 5%. Thus, both methods can be employed in the analysis of fusidic acid in pharmaceutical form of dermatological cream in the pharmaceutical ...